Optimization of Power Consumption for the Design of 802.11n MIMO_OFDM System (Journal of University of Babylon for Engineering Sciences, 2018)
In modern systems communication, different methods have been improved to change the prior imitative techniques that process communication data with high speed. It is necessary to improve (OFDM) Orthogonal Frequency Division Multiplexing technique because the development in the guideline communication of wireless system which include security data and transmission data reliability. The applications communications of wireless is important to develop in order to optimize the process of communication leads to reduce the level consumption energy of the output level signal. The architecture of VLSI is used to optimize the performance transceiver in 802.11 n OFDM-MIMO systems, this idea concentrate on the design of 6x6 MIMO_OFDM system in software simulink of MATLAB then using generator system for transfer to code of VHDL and applying in FPGA Xilinx Spartan 3 XC3S200 . The modelsim used to get the simulation while Xilinx power estimator is used to calculate power. The results registered total power consumption about 94mW while compared with previous work  was 136mW which means a high reduction of about 30.8% .